2010
DOI: 10.1111/j.1745-4573.2010.00221.x
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of the Antioxidant and Antimicrobial Effectiveness of Different Forms of Garlic and Bha in Emulsion‐type Sausages During Refrigerated Storage

Abstract: The antioxidant and antimicrobial effects of each of different forms of garlic and BHA in emulsion-type sausage at 4C for 0, 10, 20 and 30 days were investigated. The treatments were divided into five groups: control, 30 g of fresh garlic /kg of sausage, 9 g of garlic powder /kg of sausage, 100 mL of garlic extract/kg of sausage and 0.1 g of BHA/kg of sausage. pH, peroxide value (POV), thiobarbituric acid reactive substance (TBARS), residual nitrite contents (RN) and total aerobic plate count (TAPC) were evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 25 publications
(36 reference statements)
2
9
0
Order By: Relevance
“…The highest hardness value for garlic incorporated smoked fillets is may be due ability of garlic to retard the development of peroxide values that is responsible for the increased tenderness. This conclusion was supported by the observation of a negative correlation between peroxide value and tenderness attribute [21,22], while the lowest hardness values for control and ginger incorporated smoked fillets samples during frozen storage could be resulted from, enzymatic degradation that induces many physical mechanisms, among them gaping, which contributes to muscle tenderization. Proteases involved are primarily calpains, cathepsins, and collagenases.…”
Section: Texture Profile Analysis (Tpa)supporting
confidence: 63%
See 1 more Smart Citation
“…The highest hardness value for garlic incorporated smoked fillets is may be due ability of garlic to retard the development of peroxide values that is responsible for the increased tenderness. This conclusion was supported by the observation of a negative correlation between peroxide value and tenderness attribute [21,22], while the lowest hardness values for control and ginger incorporated smoked fillets samples during frozen storage could be resulted from, enzymatic degradation that induces many physical mechanisms, among them gaping, which contributes to muscle tenderization. Proteases involved are primarily calpains, cathepsins, and collagenases.…”
Section: Texture Profile Analysis (Tpa)supporting
confidence: 63%
“…However, after day 6 of storage, the SEP content in garlic treated (T4 andT3) samples were significantly (P < 0.05) higher than in the C, T1 and T2 samples. From the SEP results, noted that addition of ginger in a samples resulted to largest SEP loss throughout the storage time, compared to control samples, this result indicated that the higher protein denaturation and damage associated with the proteolytic activity of ginger incorporated [2,20].The antioxidant efficiency of garlic is due to rich in organsulfur compounds and their precursors (allicin, diallyl sulfide and diallyl trisulfide) have biological actions to retard lipid oxidation [14,22,37], resulted to lowest SEP loss throughout the storage time for garlic incorporated samples, compared to control and ginger treated samples, since interaction between protein and lipid oxidation products, causing a decline of protein solubility [3,34]. The decrease in SEP for control samples during frozen storage could be resulted from the formation of hydrogen or hydrophobic bonds, as well as disulfide bonds and ionic interactions [5,32,36].…”
Section: Salt Extractable Proteinmentioning
confidence: 85%
“…Most of volatile compounds have been previously detected (Marco et al 2008;Gianelli et al 2009), except for those compounds provided by the spices and the smoking process. All the sulphur compounds that were identified in the samples came from garlic (Calvo-Gómez et al 2004 (Kim et al 2010). The presence of higher percentage of garlic volatile compounds showed that this product in particular was formulated with higher amounts of garlic, and therefore it might have a higher antimicrobial activity.…”
Section: Longaniza Sausagesmentioning
confidence: 99%
“…Fresh garlic was prepared following the procedure previously described by Kim et al (2010). Briefly, fresh garlic was peeled, cut into slices, and subsequently thinly spread on a mat in direct sunlight at 30 to 35 o C to make garlic powder.…”
Section: Methodsmentioning
confidence: 99%
“…The percentages of the basic components in the sausages were as follows: ground pork meat (60%), fat (20%), cornstarch (6%), sausage seasoning (3%, Taewon Food Industry CO., Ansan, South Korea), salt (1.5%), polyphosphate (0.25%), and ice water (10%). Emulsion-type sausages were manufactured as described by Kim et al (2010). Briefly, all other ingredients were thoroughly mixed with the various formulations of sausage meat in the cutting chopper.…”
Section: Sausage Makingmentioning
confidence: 99%